Prevalence of mental health problems in women in polygamous versus monogamous marriages: a systematic review and meta-analysis - Rahmanian, Parisa; Munawar, Khadeeja; Mamat Mukhtar, Firdaus; Choudhry, Fahad Riaz (Springer, 2020)
While some studies suggest different mental health outcomes among women in polygamous versus monogamous marriages , no published systematic review or meta-analysis has analyzed the relevant research literature. This article aims to review the evidence of marriage types (i.e., polygamous and monogamous marriages ) and differences in the prevalence of mental health issues. Eleven electronic databases, along with further identified references lists, were searched. Thirteen studies met the inclusion criteria. They included 3166 participants, and 986 women were in a polygamous marriage . All studies were rated for quality and were tested for publication bias. Meta-analyses were conducted on the five symptoms to assess for the effect of marriage type. The studies indicate a significant association of marriage type with psychological symptoms. The metaanalysis indicates that women in polygamous marriage had worsened mental health as compared with women in monogamous marriages . The weighted mean differences with 95% confidence intervals were somatization 0.53, 0.44–0.63; obsession-compulsion 0.35, 0.14–0.56; interpersonal sensitivity 0.42, 0.12–0.73; depression 0.41, 0.15–0.67; anxiety 0.41, 0.15–0.68; hostility = 0.47, 0.28–0.66; phobic anxiety 0.39, 0.17–0.61; paranoid ideation 0.35, 0.24–0.47; psychoticism 0.41, 0.23, 0.59; and Global Severity Index (GSI) 0.43, 0.25–0.60. A higher self-esteem and life satisfaction among women in polygamous marriages and statistically superior family functioning among women in monogamous marriages were also found. However, there was no statistically significant difference between the marital satisfaction of women in polygamous versus monogamous marriages . Results are consistent with the existing research on the prevalence of mental health issues among women in polygamous marriages . Nonetheless, these women were found to have elevated self-esteem and life satisfaction than women in monogamous marriages . Directions for future research are indicated.